Site-Directed Mutagenesis of the Carotenoid Isomerase Gene BnaCRTISO Alters the Color of Petals and Leaves in Brassica napus L. - Li, Huailin; Yu, Kaidi; Amoo, Olalekan; Yu, Yalun; Guo, Mixia; Deng, Songyue; Li, Mengting; Hu, Limin; Wang, Jingzhen; Fan, Chuchuan; Zhou, Yongming (Frontiers in Plant Science, 2022)
The diversity of petal and leaf color can improve the ornamental value of rapeseed and promote the development of agriculture and tourism. The two alleles of carotenoid isomerase gene (BnaCRTISO) in Brassica napus (BnaA09.CRTISO and BnaC08.CRTISO) was targeted and edited using the CRISPR/Cas9 system in the present study. Double mutants of BnaCRTISO show creamy white petals and yellow leaves phenotype. The carotenoid content in the petals and leaves of the BnaCRTISO double mutant was significantly reduced. In contrast, some carotenes content (Lycopene, α-Carotene, γ -Carotene) increased significantly in petals while the chalcone content, a vital substance that makes up the yellow color, also decreased significantly. Further, transcriptome analysis showed that the targeted mutation of BnaCRTISO resulted in the significant down-regulation of important genes BnaPSY and BnaC4H in the carotenoid and flavonoid synthesis pathway respectively; however, the expression of other related genes was up-regulated. This indicates that the molecular mechanism regulating petal color change in B. napus is more complicated than those reported in Arabidopsis and other Brassica species. In summary, our findings reveal the involvement of BnaCRTISO copies in the regulation of petal and leaf color and provides valuable resources for rapeseed breeding.